A Study of the Difference between Imagining and Imagination in Ibn Arabi’s Meccan Illuminations - nafiseh ahl sarmadi; nosratollah hekmat (حکمت و فلسفه, 2013)
As one of the important branches of philosophy, anthropology mainly discusses mankind’s internal and external perceptions. Imagination (al-khyāl) and imagining (al-takhayyol) are part of mankind’s internal perceptions. The majority of philosophers consider imagination to be passive and imagining active. While believing in passive imagination as the nest of senses, Ibn Arabi puts forward the idea of active imagination as the homeland of truth and collection of paradoxes and, thus, the most similar being to God. In many cases, he uses imagination and imagining synonymously. However, this does not mean that they are not different. Comparing imagination to the cane of Moses and imagination to the magic of sorcerers, discussing the errors of imagination and believing in imagining as an illusory affair help one to distinguish between them.